Awal Mula Kemampuan Berkomunikasi: Sebuah Tinjauan Communibiology - Fajar, Dewanto Putra; Aminulloh, Akhirul (Tuturlogi: Journal of Southeast Asian Communication, 2023)
Humans become social creatures who develop complex communication behavior as a means of social interaction. The ability to communicate in humans basically involves a number of important aspects in humans, which develop gradually, starting from the most fundamental aspects, namely genetic aspects, to the highest aspects, namely aspects of nurture and learning. In addition, the ability to communicate in humans emerges and develops according to the level of development of the human brain. Simply put, human communication skills involve many important aspects which all complement one another. The loss of one aspect in shaping the communication process reduces the effectiveness of the communication process, leading to communication failures. This journal article uses the perspective of communibiology to examine a number of factors relating to the origin of the human ability to communicate to the implications surrounding the human ability to communicate. Thus, all parties involved in the communication process can maximize the communication process, by minimizing the emergence of factors that reduce the effectiveness of the communication process.